Relationship of knowledge and attitude with smoking habits at low healthy family index - Aisyah Lahdji; Hema Dewi Anggraheni; Nina Anggraeni Noviasari; Muhammad Ridhwan Hamdan (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
Smoking is one of the habits that are often done by the people of Indonesia. Smoking habits are influenced by several things, such as knowledge and attitudes. Having good knowledge will tend to avoid smoking habits, and having a positive attitude will make someone stop smoking. This study aims to determine the relationship between knowledge and attitudes toward smoking habits in Tugu District residents with a Low Healthy Family Index. This research is an observational study with a cross-sectional approach carried out in Tugu District with residents with a low Healthy Family Index. The samples used were 81 samples. The analysis used is the Spearman test. The results showed that 34 respondents (42%) had sufficient knowledge, 64 respondents had a negative attitude (79%), 36 respondents were heavy smokers (44.4%), and 45 respondents were moderate smokers (55.6%). The results of the relationship between knowledge and attitudes toward smoking habits are each with p values of 0.000 and 0.005. This study concludes that there is a relationship between knowledge and attitudes toward smoking habits in Tugu District residents with a Low Healthy Family Index.